Model Pembelajaran Bahasa Arab Berbasis Kebutuhan Mahasantri Pesantren Mahasiswa - Alawiyah, N. Lalah; Muttaqin, Zainal; Taqi, Anas Zein (Kalimatuna: Journal of Arabic Research, 2022)
This study aims to describe 1) students' perceptions of the purpose of learning Arabic in terms of its relevance to their learning needs; 2) female students' perceptions of Arabic teaching materials; 3) language skills (listening, speaking, reading, and writing) which are priorities and student required;; and 4) Evaluation of the desired learning. To achieve this goal, the research approach that is considered relevant in this research is a qualitative approach with a case study approach. Data were collected through questionnaires and interviews. The research results obtained are: 1) The objectives to be achieved by students are the ability to read and understand lecture material sourced from Arabic books. 2) The subject matter desired by students is related to listening, speaking, and reading skills, and relates to linguistic elements consisting of sounds, vocabulary (mufradat) word forms, and sentence structures that suit the needs (tanzhim psychology). 3) Taking into account the objectives and material above, various eclectic methods can be used with an emphasis on the touchable grammar method (thariqah qawa'id wa tarjamah) and the reading method. To practice speaking skills in communicating Arabic, the sam'iyyah syafawiyah method can be used. 4) Evaluation must be carried out programmatically using various tools, especially tests, both oral and written. This test can be objective or subjective.